On the example of Karakalpak State University of reforms in higher education of the Republic of Karakalpakstan - Ikhmet Elmuratov (Zien Journals, 2021)
The article describes the reforms and changes in the field of education in the Republic of Karakalpakstan in 1990-2020, specific directions of development, increasing demand for higher education in the early days of independence, the introduction of new specialties and new education, the role of higher education and reforms at Karakalpak State University.
Keywords: Education; Reform; Politics; University